Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
1).( 27,56 x 35 ) + ( 27,56 x 67 ) - ( 27,56 x 2)
= (964 + 1846,52) - 55,12
=2810,52 - 55,12
= 2755,4
2).( 4x 35 ) x ( 25 x 5 ) x 2
= ( 140 x 125 ) x2
= 17500 x 2
=35000
4). 3/10
5). 1188
6). 61/6
Bài 1:tính
a)65.(-19)+19.(-35)
=65.(-19)+(-19).35
=(-19).(65+35)
=(-19).100
=-1900
b)85.(35-27)-35.(85-27)
=85.35-85.27-35.85+35.27
=(85.35-35.85)+(-85.27+35.27)
=27.(-85+35)
=27.(-50)
=1350
c)47.(45-15)-47.(45+15)
=47.[(45-15)-(45+15)]
=47.[30-60]
=47.(-30)
=-1410
Bài2: Tìm các số nguyên x biết
a)(-2).(x+6)+6.(x-10)=8
-2x-12+6x-60=8
4x-72=8
4x=72+8
4x=50
x=\(\frac{25}{2}\)
b)(-4).(2x+9)-(-8x+3)-(x+13)=0
-6x-36+8x-3-x-13=0
x-41=0
x=41
Bài 1: Tính
a) \(65.\left(-19\right)+19.\left(-35\right)\)
= \(-1235+-665\)
= \(-1900\)
b) \(85.\left(35-27\right)-35.\left(85-27\right)\)
= \(-1350\)
c) \(47.\left(45-15\right)-47.\left(45+15\right)\)
=\(-1410\)
Bài 2: Tìm x:
\(\left(-2\right).\left(x+6\right)+6.\left(x-10\right)=8\)
\(x=20\)
a/ ( 35-x)-25=40-(15-18)
(35-x)-25=40-(-3)
(35-x)-25=43
35-x=43+25
35-x=68
x=35-68
x= -33
b/ x+42=-15+27: 3^2
x+42=-15+27 : 9
x+42=-15+3
x+42=-12
x=-12 -42
x= -54
Bài 6:
a)\(\left(-18\right)-\left(-3\right)-12\)
\(=\left(-18\right)+3-12\)
\(=-15-12\)
\(=-27\)
b)\(85.\left(35-27\right)-35.\left(85-27\right)\)
\(=85.35-85.27-35.85+35.27\)
\(=85.\left(35-27-35\right)+35.27\)
\(=85.\left(-27\right)+35.27\)
\(=27.\left(-85+35\right)\)
\(=27.\left(-50\right)\)
\(=-1350\)
c)\(\left(-45\right).69+31.\left(-45\right)\)
\(=\left(-45\right).\left(69+31\right)\)
\(=\left(-45\right).100\)
\(=-4500\)
Bài 7:
a)\(\left(2-x\right)+10=-14\)
\(\Rightarrow2-x=-24\)
\(\Rightarrow x=26\)
b)\(14.\left|x\right|=28\)
\(\Rightarrow\left|x\right|=2\)
\(\Rightarrow\orbr{\begin{cases}x=2\\x=-2\end{cases}}\)
c)\(31-\left(17+x\right)=55\)
\(\Rightarrow17+x=-24\)
\(\Rightarrow x=-41\)
a)(x+35)-2.(-4)^2=-61
<=>x+35-32=-61
<=>x=-64
b)2^2.(-3)-(x+27)=-34
<=>-12-x-27=-34
<=>x=-5
c)3-3./x+4/=-27
<=>/x+4/=10
<=>x+4=10
x+4=-10
<=>x=6;-14
\(35-228:\left(x-3\right)^2=27\)
\(\Rightarrow288:\left(x-3\right)^2=8\)
\(\Rightarrow\left(x-3\right)^2=288:8\)
\(\Rightarrow\left(x-3\right)^2=36\)
\(\Rightarrow\left(x-3\right)^2=\left(\pm6\right)^2\)
\(\Rightarrow\orbr{\begin{cases}x-3=6\\x-3=-6\end{cases}}\Rightarrow\orbr{\begin{cases}x=6+3\\x=\left(-6\right)+3\end{cases}}\Rightarrow\orbr{\begin{cases}x=9\\x=\left(-3\right)\end{cases}}\)